Boundary problems for fully nonlinear parabolic equations with Lévy Laplacian - Feller, M. N.; Belopolskaya, Ya. I.; Albeverio, S. (Methods of Functional Analysis and Topology, 2008)
We suggest a method to solve boundary and initial-boundary value problems for a class of nonlinear parabolic equations with the infinite dimensional L’evy Laplacian Δ _L f(U(t,x),U(t,x)t,Δ_LU(t,x))=0 in fundamental domains of a Hilbert space.